Incidence of cancer in children aged 0–14 years in Taiwan, 1996–2010. Issue 1 (February 2015) - Liu, Yen-Lin; Lo, Wei-Cheng; Chiang, Chun-Ju; Yang, Ya-Wen; Lu, Meng-Yao; Hsu, Wen-Ming; Ho, Wan-Ling; Li, Meng-Ju; Miser, James S.; Lin, Dong-Tsamn; Lai, Mei-Shu
Highlights We use population-based data to analyze cancer incidence of age 0–14 in Taiwan during 1996–2010. Taiwan has a lower but increasing incidence of childhood cancer. Incidence of germ cell tumors and hepatic tumors are higher in Taiwan.